al-Ifā̤zāt : sharḥ Urdū al-Maqāmāt al-Ḥarīrī, al-ḥavāshī al-jadīdah va al-taʻliqāt al-mufīdah - Iftiḵẖār ʻAlī, Muḥammad (Maktabah-yi Shirkat-i ʻIlmiyyah, 1978)
Urdu commentary on al-Maqāmāt al-Ḥarīrīyah (Arabic classical poetry) by alḤarīrī, 1054-1122.